Exploring Blueberry Aroma Complexity by Chromatographic and Direct-Injection Spectrometric Techniques - Farneti, Brian; Khomenko, Iuliia; Grisenti, Marcella; Ajelli, Matteo; Betta, Emanuela; Algarra, Alberto Alarcon; Cappellin, Luca; Aprea, Eugenio; Gasperi, Flavia; Biasioli, Franco; Giongo, Lara (Frontiers in Plant Science, 2017)
Blueberry (Vaccinium spp.) fruit consumption has increased over the last 5 years, becoming the second most important soft fruit species after strawberry. Despite the possible economic and sensory impact, the blueberry volatile organic compound (VOC) composition has been poorly investigated. Thus, the great impact of the aroma on fruit marketability stimulates the need to step forward in the understanding of this quality trait. Beside the strong effect of ripening, blueberry aroma profile also varies due to the broad genetic differences among Vaccinium species that have been differently introgressed in modern commercial cultivars through breeding activity. In the present study, divided into two different activities, the complexity of blueberry aroma was explored by an exhaustive untargeted VOC analysis, performed by two complementary methods: SPME-GC-MS (solid phase microextraction- gas chromatography-mass spectrometry) and PTR-ToF-MS (proton transfer reaction-time of flight-mass spectrometry). The first experiment was aimed at determining the VOC modifications during blueberry ripening for five commercially representative cultivars (“Biloxi,” “Brigitta Blue,” “Centurion,” “Chandler,” and “Ozark Blue”) harvested at four ripening stages (green, pink, ripe, and over-ripe) to outline VOCs dynamic during fruit development. The objective of the second experiment was to confirm the analytical capability of PTR-ToF-MS to profile blueberry genotypes and to identify the most characterizing VOCs. In this case, 11 accessions belonging to different Vaccinium species were employed: V. corymbosum L. (“Brigitta,” “Chandler,” “Liberty,” and “Ozark Blue”), V. virgatum Aiton (“Centurion,” “Powder Blue,” and “Sky Blue”), V. myrtillus L. (three wild genotypes of different mountain locations), and one accession of V. cylindraceum Smith. This comprehensive characterization of blueberry aroma allowed the identification of a wide pull of VOCs, for the most aldehydes, alcohols, terpenoids, and esters that can be used as putative biomarkers to rapidly evaluate the blueberry aroma variations related to ripening and/or senescence as well as to genetic background differences. Moreover, the obtained results demonstrated the complementarity between chromatographic and direct-injection mass spectrometric techniques to study the blueberry aroma.